PENANGANAN KAWASAN PERMUKIMAN KUMUH (STUDI MENGENAI PEMUGARAN KAWASAN PERMUKIMAN KUMUH DI KECAMATAN SEMARANG UTARA) - Suzan Bella Rosellasari; Ari Subowo (Journal of Public Policy and Management Review, 2019)
The Semarang City Government has set a priority location for Semarang slum handling based on the Mayor of Semarang Decree No 050/801/2014 concerning the Determination of the Location of Slum Housing and Settlement Locations in the City of Semarang which establishes 62 urban-village from 15 Subdistricts. With the largest area of slum area occupied by North Semarang Subdistrict which reached an area of 147.4 Ha of the total area of 1097 Ha or has a percentage of slum area which is equal to 13.4 percent. The distribution of slum areas in North Semarang District consists of Tanjungmas urban-village, Bandarharjo urbanvillage, Panggungkidul urban-village, Kuningan urban-village, and Dadapsari urban-village. In order to deal with the problem of slum settlements activities are carried out to improve the quality of slums through a pattern of handling the restoration of slums. This study uses a qualitative descriptive method to achieve the research objectives, namely to determine the implementation of the restoration of slum areas in North Semarang District, and to identify the factors that influence the implementation of these policies through the implementation model of G. Shabbir Cheema and Dennis A. Rondinelli. From the results of the study it was found that the implementation of the restoration of slum areas in North Semarang Subdistrict was not optimal because the lack of involvement of recipients of policy, coordination and integration among sectors, especially regarding uninhabitable housing had not yet been integrated, and there were still a few unresolved points. In addition, it was found that factors that have a negative effect are non-conducive environmental conditions, ineffective relationships between organizations, and insufficient resources.